2014
DOI: 10.1371/journal.pone.0088076
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum Polysaccharides Prevent Memory and Neurogenesis Impairments in Scopolamine-Treated Rats

Abstract: Lycium barbarum is used both as a food additive and as a medicinal herb in many countries, and L. barbarum polysaccharides (LBPs), a major cell component, are reported to have a wide range of beneficial effects including neuroprotection, anti-aging and anticancer properties, and immune modulation. The effects of LBPs on neuronal function, neurogenesis, and drug-induced learning and memory deficits have not been assessed. We report the therapeutic effects of LBPs on learning and memory and neurogenesis in scopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 61 publications
4
46
0
3
Order By: Relevance
“…This means that the methanol extract of L. barbarum is more beneficial to spatial learning than control conditions and females are better at spatial memory than males. The finding that the methanol extract of L. barbarum is beneficial to spatial learning is consistent with a recent finding (Chen et al, 2014) of some beneficial effects of LBPs on learning and memory in rats. In line with this finding, this research also demonstrated that the methanol extract of L. barbarum increases spatial learning memory, especially for females.…”
Section: Spatial Memory Performancesupporting
confidence: 92%
“…This means that the methanol extract of L. barbarum is more beneficial to spatial learning than control conditions and females are better at spatial memory than males. The finding that the methanol extract of L. barbarum is beneficial to spatial learning is consistent with a recent finding (Chen et al, 2014) of some beneficial effects of LBPs on learning and memory in rats. In line with this finding, this research also demonstrated that the methanol extract of L. barbarum increases spatial learning memory, especially for females.…”
Section: Spatial Memory Performancesupporting
confidence: 92%
“…Scopolamine is thought to exert various toxic properties on the nervous system. It exhibited toxicity on the population and dendritic development of the newborn neurons and immature granular cells in dentate gyrus, which directly results in injury of the hippocampal circuits that may predominantly be responsible for cognitive and memory deficits [22]. Inhibition of the muscarinic acetylcholine receptor by scopolamine also contributes to characteristic cognitive and memory deficits of AD [23], as well as the cholinergic receptor antagonists [24].…”
Section: Discussionmentioning
confidence: 99%
“…Scopolamine is used as a standard/reference drug for inducing cognitive deficits in healthy humans and animals . It is thought to exert various toxic properties on the nervous system and also, exhibited toxicity in the population and dendritic development of the newborn neurons and immature granular cells in dentate gyrus, which directly results in injury of the hippocampal circuits that may predominantly be responsible for cognitive and memory deficits . Inhibition of the muscarinic acetylcholine receptor by scopolamine also contributes to characteristic cognitive and memory deficits of AD, as well as the cholinergic receptor antagonists .…”
Section: Introductionmentioning
confidence: 99%